Desigualdades sociais em saúde: uma abordagem metodológica - Magalhães, Kelly Lacerda de Oliveira (2012)
Social injustice affects the health causing different risks of illness and death on the basis of differences in living conditions of population groups, establishing a framework of health inequities. Studies aimed at identifying and measuring these inequities have been constituted as a major contribution to reducing them by providing subsidies for the formulation and implementation of social policies with fair character. Some authors have demonstrated the importance of applying these studies, paying special attention to social inequalities in health exist in the current epidemiology and nutrition in Brazil, which has been constituted as a result of processes of transition that the country has experienced for decades in these areas. These inequalities increase the complexity of the transitions, leading mainly in the health sector, a juxtaposition of risks that will encounter as most vulnerable segment of the population groups most disadvantaged socioeconomically, further exacerbating health inequities. In this perspective, the challenge of reducing health inequities, we have seen the increase of scientific studies aimed at the systematization of concepts and construction of methodological tools that can enhance research in this area. Seeking to contribute to the methodological development of this research, the present study, part of the issue of measuring social inequalities in health, aimed to address theclustering techniques that are used in these studies. Thus, we tried two of these techniques (Cluster Analysis and Quintiles) in the aggregate of municipalities according to the condition of life reflected by a composite indicator. These two techniques were analyzed for the ability of these groups adequately reflect the reality of social inequalities in health between the groups of brazilian municipalities. For that, through specific tests, we assessed the statistical parameters recommended in relation to the heterogeneity between clusters and the homogeneity of the same. Subsequently, we calculated a sensitive indicator of health condition of life, the rate of post-neonatal mortality for each group formed and applied an epidemiological measure, the ratio of rates to measure and compare the magnitude of social inequalities in health.The results showed that both techniques were able to meet preconization internal homogeneity of the groups and heterogeneity between them, with both showing to be effective in reflection of existing social inequalities in health. However, the ratio of rates showed that in the intermediate groups, the technique of Cluster reflected these inequalities with greater intensity, this fact may be a criterion for methodological choice for this technique. As to the technique of the quintiles, the methodological choice for the same can be based on its advantage of having greater methodological simplicity, which makes it feasible to use in everyday health services, in which the measurement of social inequalities in health should be encouraged to plan more targeted actions to promote equity.